THE DYNAMICS OF THERAPIST ATTACHMENT AS A FACTOR OF PROFESSIONAL IDENTITY - Hrechanyk, Mariia (PSYCHOLOGICAL JOURNAL, 2025)
The article presents a theoretical analysis of the dynamics of therapist attachment as a significant factor in the development of professional identity. It is argued that the therapist’s attachment patterns evolve through a complex interaction between personal, professional, and relational variables that collectively determine the quality and stability of the therapeutic alliance. The dynamics of attachment are conceptualized across three interrelated levels: personal (early attachment experiences, interpersonal relationships, capacity for self-reflection), professional (supervision, collegial support, ethical and organizational culture), and processual (countertransference reactions, degree of emotional involvement, and clinical complexity). The study highlights that the therapist’s attachment style functions as a mediating variable influencing the quality of the working alliance and the depth of therapeutic engagement. A secure attachment style facilitates trust, emotional stability, and flexibility in interaction, contributing to the maintenance of contact even in emotionally charged or challenging sessions. In contrast, anxious or avoidant attachment styles may lead to overinvolvement, emotional exhaustion, boundary violations, or excessive distancing, thereby complicating the therapeutic process. The ability of the therapist to recognize and regulate their own attachment-related responses determines how effectively they can sustain the alliance, manage countertransference, and support the client’s psychological change. The development of a psychotherapist’s professional identity is shown to depend on the level of awareness and integration of personal attachment schemas into the professional role, as well as the ability to transform emotional responses into therapeutic competence. Supervision, personal therapy, and reflective practice are identified as key mechanisms promoting the formation of secure attachment and professional maturity. The findings emphasize that the dynamics of therapist attachment represent a crucial psychological factor underlying professional identity, emotional regulation, and therapeutic efficacy. Understanding and integrating one’s own attachment dynamics allows psychotherapists to maintain authenticity, empathy, and resilience within the therapeutic relationship, thus ensuring both professional effectiveness and personal psychological well-being.